Uporaba fitofarmacevtskih sredstev in varovanje voda na vodovarstvenih območjih - Lešnik, Mario (2017)
The Use of Plant Protection Products and the Protection of Water at Water Protection Zones. The monograph was prepared to educate agricultural advisors and farmers on the ways of pollution of ground and surface water with plant protection products (PPP) and to present the techniques for the prevention of their water pollution. It was prepared for the project SI-MUR-AT, an EU Cooperation Program INTERREG Slovenia-Austria 2014 – 2020. In the first part, the transition paths of PPP into the water are presented (leaching through the profile of the soil, surface run-off and point source pollution). The importance of soil’s pedological and hydrological characteristics for limiting PPP leaching and the methods for reducing the passage of PPP into the water are also presented. These are: the modified methods of PPP use and of rotation with preparations, improved risk analysis for leaching and runoff of PPP, changed methods of soil tillage, adapted application methods of PPP in the vicinity of surface water to reduce drift,  retention measures for prevention of water runoff from arable land into the drain ditches and increased use of mechanical methods of weed control.
Keywords: plant protection products; ground water; surface water; protection; measures; cropping techniques; field crops